2016
DOI: 10.1002/mds.26578
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Measurements of Cerebrospinal Fluid Biomarkers in Parkinson's Disease

Abstract: ObjectiveThe purpose of this study was to investigate whether cerebrospinal fluid (CSF) levels of tau, phosphorylated tau, β‐amyloid42, α‐synuclein, neurofilament light, and YKL‐40 change over time and if changes correlate with motor progression and/or cognitive decline in patients with PD and controls.MethodsWe included 63 patients with PD (nondemented) and 21 neurologically healthy controls from the prospective and longitudinal Swedish BioFINDER study, all of whom had clinical assessments and lumbar puncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(70 citation statements)
references
References 50 publications
8
61
1
Order By: Relevance
“…Moreover, immune response and inflammatory factors have an impact on NMS diversity in PD as well . Increased inflammatory factors were associated with cognitive decline, rapid eye movement sleep behavior disorder, fatigue, and depression in a previous study . Because sLAG‐3 is an indicator of cellular immunity related to cytokine secretion, it could reflect the degree of inflammatory response in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, immune response and inflammatory factors have an impact on NMS diversity in PD as well . Increased inflammatory factors were associated with cognitive decline, rapid eye movement sleep behavior disorder, fatigue, and depression in a previous study . Because sLAG‐3 is an indicator of cellular immunity related to cytokine secretion, it could reflect the degree of inflammatory response in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of studies have focused on fluid biomarkers for Parkinson's disease (PD) using easily accessible sample sources such as serum and include α‐synuclein (α‐syn), DJ‐1, dopamine metabolites, factors related to oxidative stress, and inflammatory cytokines . However, the results of these studies were inconsistent with previous studies .…”
mentioning
confidence: 99%
“…In one study of CSF biomarker change with time, Hall et al . 102 found that levels of t-tau, p-tau, total α-synuclein, neurofilament and YKL-40 (a marker of inflammation), but not Aβ 42 , increased over a 2-year period and were associated with worsening cognition, and the increase was particularly marked in patients with longer disease duration. These findings are consistent with reports that α-synuclein levels increase with more severe neurodegeneration.…”
Section: Biomarkers Of Cognitive Decline In Pdmentioning
confidence: 95%
“…We recently reported that CSF α‐syn levels in de novo PD showed minimal change over 12 months . Longitudinal changes in CSF α‐syn and other biomarkers have been examined in other PD cohorts for up to 2 years with discrepant findings . Subject selection, preanalytical factors, and different assays may have contributed to discrepancies (see Discussion).…”
mentioning
confidence: 99%